Evaluation of bactericidal effects of ultraviolet light C irradiation on cariogenic bacteria: An in vitro study - Moayyad Alharbi; Fahad Bakitian; Ali Alenezi (BMC, 2021)
Abstract Backgrounds Ultraviolet light C (UVL-C) irradiation has demonstrated an antimicrobial action against various pathogens. This study aimed to evaluate the bactericidal effect of UVL-C irradiation against cariogenic oral bacteria (Streptococcus mutans) in single layers and colonies grown on solid surfaces. Methods Two different experiments were performed. In the first experiment, a single layer of Streptococcus mutans bacteria on agar plates was exposed to UVL-C irradiation at energies from 0 to 21 mWs/cm2. The second experiment was conducted to inhibit viability of bacterial colonies on solid surfaces. The samples were derived from saliva from a patient where bacteria were grown on plastic strips and then exposed to UVL-C. The highest energy was 1050 mWs/cm2. Results Exposure to 21 mWs/cm2 was bactericidal in single layers of Streptococcus mutans. The result for bacterial colonies on solid surfaces indicated only a bacteriostatic effect, even at energies of 1050 mWs/cm2. Conclusions Ultraviolet light C exhibits bactericidal effects on single layers of Streptococcus mutans but has a limited effect on bacterial colonies in a biofilm. It is a matter of debate whether these in vitro results would have the same effect in clinical setting.